Analysis of Learning Management System Usage in Elementary Schools in The Digital Era - Shulkhah; Sofyan Mustoip; Rahayu Amelia; Somantri (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2025)
The rapid advancement of digital technology has significantly influenced education, including the adoption of Learning Management Systems (LMS) in elementary schools. This study aims to analyze the usage of LMS in elementary education, focusing on its implementation, benefits, challenges, and impact on teaching and learning processes. A qualitative research approach was employed, using interviews and observations to gather data from teachers, administrators, and students across several elementary schools in urban and rural settings. The findings reveal that LMS usage enhances learning flexibility, improves access to educational resources, and supports individualized instruction. However, challenges such as limited digital literacy among teachers, insufficient infrastructure, and resistance to change hinder optimal adoption. The study concludes that while LMS has transformative potential, its effectiveness depends on adequate training, infrastructure support, and integration with existing curricula. The research highlights the need for policies promoting teacher digital competency and investment in technological infrastructure to maximize the benefits of LMS in elementary education. This study provides valuable insights for educators, policymakers, and stakeholders to enhance digital education strategies, ensuring they are inclusive and effective in addressing the diverse needs of elementary school students in the digital era.